Early opportunities and fourth-grade success: State pre-k funding, quality, and access on student achievement - Pendola, Andrew; Muñoz, Ismael; Zapata, Mayli; Schaub, Maryellen (Education Policy Analysis Archives, 2022)
To ensure all children can be successful in school and beyond, states have increasingly supported and expanded pre-kindergarten (pre-k) programs aimed and improving student outcomes and reducing disparities. While research has shown generally positive short-term outcomes for specific programs, state design and support for pre-k programs varies widely across the US, making cross-state comparisons difficult. As a means to better inform state policy decisions, this study assesses the relation between structural aspects of pre-k programs on fourth-grade student achievement and gaps across all 50 states. In assessing the relation of ELA achievement with state funding, standards of quality, and scope of access, we find that (1) state funding is associated with both increases in student achievement and reduced gaps, (2) the effect of funding is stronger in states that provide targeted pre-k access to low-income/at-risk students, and (3) legislated quality standards only improve overall achievement in states that provide universal access to pre-k. These results help identify how state policy structure may best be used to leverage achievement benefits for pre-k programs and reduce disparities.